A New DC Model for Transmission Loss Allocations in Power Systems - Kabir, MH (Bangladesh Journal of Scientific and Industrial Research, 2008)
Under open access environment in the era of deregulated power industry, transmission loss allocation to various transactions is one of the important issues to be solved exactly. Because of the non-linear nature of power flow and power loss, it is very difficult to segregate and to allocate losses among the participants properly. This paper presents a New DC method (NDC) where an efficient loss allocation algorithm has been applied. Considering the impact of every line flow in a network, the loss allocations to the loads have been computed at first and finally the total loss has been allocated to the generators. The effectiveness of this procedure has been studied for the 6-bus and IEEE 118-bus model power systems. Several numerical analyses implicate that the proposed loss allocation procedure including the DC load flow model is reasonably acceptable. Keywords: Transmission loss allocation DC load flow model, Deregulated power market Bangladesh J. Sci. Ind. Res. 42(3), 257-268, 2007